Bidirectional Battery Charger for PV Using Interleaved Fourport DC-DC Converter - A. Elamathy; G. Vijayagowri; V. Nivetha (Indonesian Journal of Electrical Engineering and Computer Science, 2015)
In this paper, a four-port bidirectional dc-dc converter is proposed for grid-interactive photovoltaic (PV) system application. The four-phase topology is suitable for residential pumping, aerospace power requirements. The control of battery and different capacities of PV modules are naturally decoupled. In addition, the port interface with PV is current type which can implement maximum power point tracking (MPPT) and soft switching under wide variation of PV terminal voltage. Finally, simulation results are proposed to verify the power control in different operation modes. DOI: http://dx.doi.org/10.11591/telkomnika.v14i3.7894